Importance of Didactic Capabilities in Improving the Methodology of Teaching the History of National Values to Students - Andaeva Shakhnoz Sanakulovna (Scientific Trends, 2025)
This article discusses the issues of improving the methodology of teaching the history of national values to students and the importance of using didactic opportunities in this process. Also, the ways of forming and strengthening national values in the minds of students through the use of innovative methods in the modern educational process are analyzed.
Keywords: National values, didactic opportunities, methodology, teaching methods, student, historical heritage, education.